2006
DOI: 10.1007/s10038-006-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic determinants of variability in lipid-lowering response to pravastatin therapy

Abstract: Pravastatin is mainly taken up from the circulation into the liver via organic anion-transporting polypeptide 1B1 (SLCO1B1 gene product). We examined the contribution of genetic variants in the SLCO1B1 gene and other candidate genes to the variability of pravastatin efficacy in 33 hypercholesterolemic patients. In the initial phase of pravastatin treatment (8 weeks), heterozygous carriers of the SLCO1B1*15 allele had poor low-density lipoprotein cholesterol (LDL-C) reduction relative to non-carriers (percent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…The attenuation of response in the CC homozygotes was larger than that seen in the SEARCH study but the number of CC participants was small and the differences were not statistically significant. Our results contrast with three studies of pravastatin that showed larger attenuations of the pravastatin response in the TC heterozygotes (total cholesterol reductions of 13.1% in TCs vs. 19.1% in TTs [3], 9.8% in TCs vs. 20.9% in TTs [4] and 14.5% in TCs vs. 22.4% in TTs [5]), which were statistically Short report significant in two out of the three studies [3][4][5]. Differences in the timing of lipid measurements and the ethnicity of the study populations may have contributed to the contrast in results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The attenuation of response in the CC homozygotes was larger than that seen in the SEARCH study but the number of CC participants was small and the differences were not statistically significant. Our results contrast with three studies of pravastatin that showed larger attenuations of the pravastatin response in the TC heterozygotes (total cholesterol reductions of 13.1% in TCs vs. 19.1% in TTs [3], 9.8% in TCs vs. 20.9% in TTs [4] and 14.5% in TCs vs. 22.4% in TTs [5]), which were statistically Short report significant in two out of the three studies [3][4][5]. Differences in the timing of lipid measurements and the ethnicity of the study populations may have contributed to the contrast in results.…”
Section: Discussioncontrasting
confidence: 99%
“…The largest study was by the SEARCH group who showed a small although statistically significant decrease in the LDL-cholesterol lowering response in carriers of the rs4149056 rare C allele (LDL reductions 1.28% Ϯ 0.25% smaller per copy of the SNP, P < 0.0001) after dosing with 40 mg simvastatin [2]. This contrasts with three small studies of pravastatin showing larger effects of rs4149056 on the lipid lowering response [3][4][5]. Simvastatin is given as a lactone prodrug but only the acid form of the drug is transported by OATP1B1 [6].…”
Section: British Journal Of Clinical Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a lower LDL-cholesterol response (−1.28% per allele) has been reported for simvastatin by the SEARCH collaborative group [14]. It has been suggested previously that the SLCO1B1 genotype is only predictive of a slower response to pravastatin treatment as genotype-associated reduction in TC was only observed in the assessment after 8 weeks, but not after a 1-year treatment [42]. Furthermore, a population-based survey showed an influence of genetic variants in the efflux transporter ABCB1 genotype on simvastatin efficacy in men by showing that previously identified SNPs are associated with larger reduction of lipid parameters than carriers of the wild-type haplotype [43].…”
Section: 9%supporting
confidence: 52%
“…Takane et al 51 reinforce the importance of knowing when cholesterol data were obtained. They conducted a retrospective analysis of 33 Japanese hypercholesterolaemic patients treated with pravastatin.…”
Section: Pharmacodynamic Studiesmentioning
confidence: 95%